Some Operators on Interval Valued Intuitionistic Fuzzy Sets of Second Type - R. Srinivasan, K. Rajesh (International Journal of Scientific Research and Management (IJSRM), 2017)
In this paper, we define some operators on Interval Valued Intuitionistic Fuzzy Sets of Second Type and establish some of their relations.